Allocation and validation of the second revision of the International Staging System in the ICARIA-MM and IKEMA studies - Richardson, Paul G; Perrot, Aurore; Mikhael, Joseph; Martin, Thomas; Beksac, Meral; Spicka, Ivan; Capra, Marcelo; D'Agostino, Mattia; Sonneveld, Pieter; Bisht, Kamlesh; Fukao, Taro; Zhang, Rick; et al. (Blood cancer journal, 2024)
The International Staging System for multiple myeloma recently underwent a second revision (R2-ISS) to include gain/amplification of 1q21 and account for the additive prognostic significance of multiple high-risk features. The phase 3 ICARIA-MM (isatuximab-pomalidomide-dexamethasone vs. pomalidomide-dexamethasone) and IKEMA (isatuximab-carfilzomib-dexamethasone vs. carfilzomib-dexamethasone) studies provide large datasets for retrospectively validating the prognostic value of the R2-ISS in relapsed/refractory multiple myeloma. Of 609 pooled patients, 68 (11.2%) were reclassified as R2-ISS stage I, 136 (22.3%) as R2-ISS stage II, 204 (33.5%) as R2-ISS stage III, 55 (9.0%) as stage IV, and 146 (24.0%) "Not classified". Median progression-free survival was shorter among those reclassified as R2-ISS stage II (HR 1.52, 95% CI 0.979-2.358), stage III (HR 2.59, 95% CI 1.709-3.923), and stage IV (HR 3.51, 95% CI 2.124-5.784) versus stage I. Adding isatuximab led to longer progression-free survival versus doublet therapy (adjusted HR 0.544 [95% CI 0.436-0.680]), with a consistent treatment effect observed across all R2-ISS stages. This is the first study to validate the R2-ISS with novel agents, including anti-CD38 monoclonal antibodies, and to show that R2-ISS, as a prognostic scoring system, can be applied to patients with relapsed/refractory multiple myeloma.
Keywords: Oligopeptides; dospělí; Female; thalidomid; Thalidomide; Adult; ženské pohlaví; lidé; staging nádorů; mnohočetný myelom; oligopeptidy; Antineoplastic Combined Chemotherapy Protocols; prognóza; protokoly protinádorové kombinované chemoterapie; retrospektivní studie; Male; Aged; dexamethason; Dexamethasone; Prognosis; lidé středního věku; humanizované monoklonální protilátky; Multiple Myeloma; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; Retrospective Studies; Middle Aged; Neoplasm Staging; Humans